IMPLEMENTASI PENDIDIKAN KARAKTER BERBASIS KEGIATAN DI MIN 1 BOYOLALI - Mahmudah, Mia Rosiana; Muh Wasith Achadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to analyze the implementation of character education based on activities at MIN 1 Boyolali. The study employs a qualitative approach with a case study design. The research subjects consist of teachers selected purposively because they are directly involved in implementing the character education program. Data collection techniques include in-depth interviews, non-participant observation, and documentation, while data analysis uses an interactive model encompassing data reduction, data presentation, and drawing conclusions. Data validity is ensured through source and method triangulation. The research findings indicate that the implementation of character education is carried out systematically and integrated with the madrasah's vision through intracurricular, cocurricular, and extracurricular activities such as Dhuha prayer, Al-Qur'an tadarus, daily infaq, outing class, and anti-bullying declaration. The program involves the madrasah principal, teachers, homeroom teachers, and parents as partners in character building. This implementation has a positive impact on enhancing students' religious attitudes, discipline, and social concern, although it still faces challenges such as limited time, number of teachers, and large number of students.